4‐Hydroxycinnamic acid suppresses airway inflammation and mucus hypersecretion in allergic asthma induced by ovalbumin challenge. (13th November 2019) - Ko, Je‐Won; Kwon, Hyung‐Jun; Seo, Chang‐Seob; Choi, Seong‐Jin; Shin, Na‐Rae; Kim, Sung‐Hwan; Kim, Yong‐Hyun; Kim, Jong‐Choon; Kim, Min‐Seok; Shin, In‐Sik
Abstract : In this study, we investigated whether 4‐hydroxycinnamic acid (HA) has a palliative effect on asthmatic inflammatory responses using a mouse model of ovalbumin (OVA)‐induced allergic asthma. The mice were divided into five groups, each consisting of seven females (normal control phosphate‐buffered saline); OVA (OVA sensitization/challenge); dexamethasone (DEX, OVA sensitization/challenge + dexamethasone 3 mg/kg); HA‐10 and HA‐20 OVA sensitization/challenge + HA 10 and 20 mg/kg, respectively). Mice treated with HA showed a reduction in airway hyperresponsiveness and in the number of inflammatory cells in bronchoalveolar lavage fluid (BALF) compared with asthmatic control. HA treatment also reduced the levels of interleukin (IL)‐5 and IL‐13 in BALF and of OVA‐specific immunoglobulin E in the serum compared with asthmatic control. HA treatment relieved airway inflammation and mucus overproduction caused by OVA exposure. Additionally, HA inhibited the increases in levels of nuclear factor kappa B, inducible nitric oxide synthase, and cyclooxygenase‐2 that normally occur after OVA exposure. HA treatment also reduced the activity and protein level of matrix metalloproteinase‐9. Taken together, HA effectively suppressed asthmatic airway inflammation and mucus production caused by OVA exposure. These findings indicate that HA has the potential to be used as a therapeutic agent for asthma.